Legal Protection for Child Victims of Exploitation in Criminal Acts of Theft - Royani, Achmad; Muljono, Bambang Eko; Shefirah, Renny Dea (Jurnal Independent, 2025)
ABSTRACT This research is motivated by child victims of exploitation in the crime of theft. During the growth period of children, both physically and mentally, they need proper care and protection in accordance with applicable legal provisions. This type of research method uses normative juridical research using statutory approaches and conceptual approaches. From the above writing, it can be concluded that the legal protection of child victims of exploitation in the crime of theft is very important. Because children are categorized as victims of exploitation, they are used as perpetrators of theft by adults. In this case, the form of legal protection using diversionary settlement is regulated in Law Number 11 of 2012 concerning the Child Criminal Justice System and regulated in Article 59A as intended by Article 59 Paragraph (1) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection.